2020
DOI: 10.1016/j.aohep.2019.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Multiple therapeutic targets in rare cholestatic liver diseases: Time to redefine treatment strategies

Abstract: Primary biliary cholangitis and primary sclerosing cholangitis are rare diseases affecting the bile ducts and the liver. The limited knowledge of their pathogenesis leads to limited therapeutic options. Nevertheless, the landscape of novel therapies for these cholangiopathies is now rapidly changing, providing new treatment opportunities for patients and clinicians involved in their care. The aim of this review is to summarize the evidence of novel molecules under investigation for primary biliary cholangitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 135 publications
(162 reference statements)
0
13
0
Order By: Relevance
“…After four weeks, interim analysis showed a dose-dependent reduction in GGT, ALP, and hepatocellular damage (ALT). Therefore, this study indicates the potential benefit of Tropifexor in PBC, and further studies are warranted [45].…”
Section: Non-bile Acids Fxr Agonistsmentioning
confidence: 72%
See 3 more Smart Citations
“…After four weeks, interim analysis showed a dose-dependent reduction in GGT, ALP, and hepatocellular damage (ALT). Therefore, this study indicates the potential benefit of Tropifexor in PBC, and further studies are warranted [45].…”
Section: Non-bile Acids Fxr Agonistsmentioning
confidence: 72%
“…Finally, at the end of 2018, the ENHANCE trial started. It was a 52-week, double-blind, placebo-controlled, randomized phase 3 study that included subjects with PBC and an inadequate response to UDCA or intolerance to UDCA ("ENHANCE: Seladelpar in Subjects With Primary Biliary Cholangitis (PBC) and an Inadequate Response to or an Intolerance to Ursodeoxycholic Acid (UDCA)", NCT03602560) [45]. Unfortunately, the open-label extension phase of this study was suspended after the onset of a similar trial evaluating the role of Seladelpar in NASH that found the occurrence of interface hepatitis in histological specimens.…”
Section: Ppar Agonistsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, only a few pharmacological therapies have been proven to be effective and only in limited pathology conditions (urosodeoxycholic acid, obeticholic acid, and bezafibrate in primary biliary cholangitis), while the vast majority of cholangiopathies are still orphan. Liver transplantation remains the only option when the disease is advanced (8)(9)(10). Major efforts for developing effective therapeutic strategies in cholangiopathies should be devoted to halt biliary fibrogenesis (4,11).…”
Section: Introductionmentioning
confidence: 99%